Investigação experimental da influência de parâmetros de usinagem sobre a resistência mecânica de um aço ferramenta endurecido - Gandia, Guilherme Caselato (Universidade Federal de São Carlos, 2020)
The manufacturing process, the machinability of a material, its mechanical properties and application purposes are recurrent subject of analysis. However, not always the machining parameters influences are taken into account, might effect the product efficiency and life-cycle. In this context, study opportunities emerge to the Surface Engineering, going deeper on the manufacturing process effects over the surface integrity. This present work delves into the influence of the turning parameters on the mechanical properties of the hardened O1 tool-steel. The investigation was based on: manufacture specimens from annealed tool-steel bars, heat-treat it and do the finishing with different settings of turning parameters, varying the feed rate and cutting speed in a complete 2^2 factorial design, measure the surface roughness and perform tensile tests. It was found that the Ra and Rz parameters showed the decrease tendency with the increase of the cutting speed (35% in average for the lowest feed rate and 5,4% for the highest) and aggravate (in average, 18,8% for the lowest cut speed and 72% fot the highest) with the feed rate increasing, although this was only statisticaly attested for the influence of the feed rate and cutting speed over the Rz. Moreover, the ultimate tensile strenght and the elongation percentage exhibit the same tendency of amplify with the increase of cutting speed (in average, 18% for the lowest feed rate and 10% for the highest) and decrease with the feed rate increasing (18,5% in average for the lowest cut speed and 10% for the highest), nonetheless this was statisticaly evidenced only for the feed rate affect over the ultimate tensile strenght. Furthermore, it was possible to establish a correlation between the Rz roughness parameter and the ultimate tensile strenght through a logarithmic regression (R2=0,7074), indicating that lower roughness values would lead to higher mechanical strenght values.
Experimental investigation of the influence of machining parameters over the mechanical strength of a hardened tool steel
Keywords: Torneamento; Velocidade de corte; Avanço; Ensaio de tração; Rugosidade; ENGENHARIAS::ENGENHARIA MECANICA